(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Epigastric, umbilical, spigelian, parastomal, and incisional hernias are several types of ventral hernias. Epigastrium and umbilical area hernias are regarded as main ventral hernias. Hernias can be repaired in a number of methods, but the tension-free repair is still the most crucial. Prior to placing mesh transabdominally, which should be of the right size and kind, the contents of the hernia are first repositioned back into the abdomen in order to do a repair by laparoscopy. Methods: The goal of the current study, which is a prospective observational one, is to analyse and assess the results of ventral hernia repairs using laparoscopic and open surgery that were presented to the Himalayan Hospital over a one-year period. Results: According to the study, the majority of cases—which were documented in the 25– 50 age range (mean: 46 years)—were involving females. The most frequent hernias were umbilical (46.2%), incisional (28.3%), paraumbilical(22.3%), and epigastric) (2.9%). The most prevalent comorbidity was diabetes mellitus (87.7%), followed by hypertension (63.8%). When compared to open surgery, there was a statistically significant difference in VAS score between patients who underwent laparoscopic surgery. Additionally, a substantial difference between the surgical process and mobilisation period was seen. Conclusion: Less post-operative discomfort, fewer complications, a shorter hospital stay, and a quicker return to regular activities are all benefits of ventral hernia surgery performed laparoscopically.